KELAYAKAN USAHA UDANG MANTIS (HARPIOSQUILLA RAPHIDEA) (STUDI KASUS UD. GAJAH MADA DI DESA LEPPE KECAMATAN SOROPIA KABUPATEN KONAWE) - Saipa, Saipa; Siang, Roslindah Daeng; Riani, Irdam; Piliana, Wa Ode; Sidiq, Azwar; Rosmawati, Rosmawati (Sultra Journal of Economic and Business, 2025)
This research aims to technically describe the mantis shrimp business in Leppe village, Soropia subdistrict, to analyze the market feasibility of the mantis shrimp bussines in Leppe village, Soropia sub-district. This research was carried out Leppe village, Soropia sub-district, konawe district in December 2023. The population in this research were business actor using the case study method. Data collecation techniques were obtained through observation, interviews, documentation and literature study. Data analysis use descriptive analysis, using the formulas for total cost, revenues, income, R/C ratio, BEP. The results of this research show that the total cost of mantis shrimp is Rp17.184.833/month, revenue is Rp23.642.857/month, profit is Rp6.458024/month, R/C ratio is 1.38. So the conclusion from the research results of the R/C ratio analysis is 1.38 that the mantis shrimp business of UD. Gajah Mada from a financial aspect which is located in the Soropia sub-district, Konawe district, is profitable or worthy of development